Social learning and health insurance enrollment: Evidence from China's New Cooperative Medical Scheme - Hong Liu; Qi Sun; Zhong Zhao (Institute for the Study of Labor (IZA), 2013)
This paper examines the role of social learning in household enrollment decisions for the New Cooperative Medical Scheme in rural China by estimating a static game with incomplete information. Using a rich dataset from the China Health and Nutrition Survey, we find that the social network effects in the enrollment decision are large and significant. Furthermore, we use temporal and spatial proximity among household heads and obtain the result that the primary mechanism for the social network effects is social learning. Our findings indicate that a 10-percentage-point increase in the enrollment rate in a village increases one's take-up probability by 5 percentage points. We also find that the importance of social learning decreases significantly with the development of alternative information channels. Finally, the evidence suggests that healthier, wealthier, relatively well-educated older male household heads with Han nationality tend to be opinion leaders.
Keywords: I1; G22; 330; rural China; health insurance; social learning; social effect